If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3878.6 = 47.3a Solving 3878.6 = 47.3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-47.3a' to each side of the equation. 3878.6 + -47.3a = 47.3a + -47.3a Combine like terms: 47.3a + -47.3a = 0.0 3878.6 + -47.3a = 0.0 Add '-3878.6' to each side of the equation. 3878.6 + -3878.6 + -47.3a = 0.0 + -3878.6 Combine like terms: 3878.6 + -3878.6 = 0.0 0.0 + -47.3a = 0.0 + -3878.6 -47.3a = 0.0 + -3878.6 Combine like terms: 0.0 + -3878.6 = -3878.6 -47.3a = -3878.6 Divide each side by '-47.3'. a = 82 Simplifying a = 82
| 25=25+5 | | 1/3x^2-1/2x=-1/6 | | h=-4.9t^2+21t+40 | | X+68=6+74 | | 234=18a | | 3sinx=1+x | | m=3/2ax-2 | | 7n-3=4n+12 | | 5r^2-34r+45=0 | | y^2=0.25 | | d/dx(3cos(2x)) | | Y=2cosx+4x-14 | | 7n+5=5n+25 | | 8d+31=3.4d+9 | | x+5=-3(x+1) | | 10x+-5=5x | | k^2=k+2 | | -9=3w-27 | | 2s-18=4 | | 5+5s=-35 | | 6w=28 | | 2x^2+y^2-2xy+12y+72=0 | | -48=6-6s | | -24=4b+32 | | 3z(z^2+2)-2(z-2)+(2z+1)= | | -3x-8=-7x+12 | | -16+10=-4x-2 | | 9+4k=1 | | x^2+4x-9forx=x+3 | | -12x+3=-10x-9 | | 60-5x=4x+18 | | -19x-9=-7x+27 |